FINANCIAL STATEMENTS TIMELINESS: THE CASE OF MALAYSIAN LISTED INDUSTRIAL PRODUCT COMPANIES - GholamReza Zandi,; Nur Amalina Abdullah, (Asian Academy of Management Journal, 2019)
Timeliness of corporate annual financial reports is a crucial factor which affects the usefulness of information made available to external users especially investors. The purpose of this study is to examine the impact of corporate governance towards companies’ performances which consequently affect the timeliness of any report submitted to the local authority. This study takes the industrial product sector and the annual reports of companies operating therein and a list of submission dates of annual report to Bursa Malaysia by Malaysian public listed companies for data analysis. Regression analyses were performed to examine the relationship between corporate governance and company’s performance using return on asset (ROA) and return on equity (ROE) which will eventually affect the timeliness submission of the annual report to Bursa Malaysia. The Chief Executive Officer (CEO) duality and independent audit committee carry a significant relationship with timeliness of financial reporting whereas 8.8% of the studied companies submit early within the statutory requirement while the remaining 91.2% submit timely.